1981
DOI: 10.1136/ard.40.6.605
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged reduction in polymorphonuclear adhesion following oral colchicine.

Abstract: SUMMARY Polymorphonuclear leucocyte (PMN) function was studied in 7 healthy subjects before and after 5 mg of colchicine taken in divided doses over 24 hours. Mean adherence to nylon fibre colums fell from a pretreatment level of 51 % to 33 -6 % by day 1, remained low (31 -8 %) at day 5, and returned to pretreatment levels only by about day 9. Random motility (agarose plate method) fell from 932 ,um to 688 ,um by day 1, but had returned to normal by day 5 hours. Blood samples were taken into heparinised contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…This study suggests that the production of oedema is dependent on PMNs since colchicine, which inhibits PMN locomotion [9] inhibited this part of the response at a dose which is inactive against arachidonic acid induced ear oedema, a PMN independent reaction [10]. The temporal relationship between oedema and PMN infiltration is not precise but as recently discussed by Forrest et al [11] this may be because PMN dependent increases in vascular permeability occur when the cells are adherent to the endothelium before they migrate into the tissues.…”
Section: Discussionmentioning
confidence: 92%
“…This study suggests that the production of oedema is dependent on PMNs since colchicine, which inhibits PMN locomotion [9] inhibited this part of the response at a dose which is inactive against arachidonic acid induced ear oedema, a PMN independent reaction [10]. The temporal relationship between oedema and PMN infiltration is not precise but as recently discussed by Forrest et al [11] this may be because PMN dependent increases in vascular permeability occur when the cells are adherent to the endothelium before they migrate into the tissues.…”
Section: Discussionmentioning
confidence: 92%
“…It was recently noted that the endothelium plays an active role in neutrophil recruitment. When studied in an in vivo model of acute inflammation, colchicine reduces the adhesion of neutrophils to the vascular endothelium [29,30]. The interaction of neutrophils and other circulating leukocytes with the vascular endothelium is mediated by several specific cell adhesion molecules on the neutrophil and the endothelial cell.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The anti-inflammatory effect of colchicine is induced by inhibition of the synthesis of tumor necrosis factor  (TNF) by macrophages and down-regulation of surface expression of TNF-receptor on macrophages and endothelial cells, thus it interferes with the priming effect of TNF on neutrophils before their activation by monosodium urate crystals (Li et al, 1996;Ding et al, 1990), inhibition of leukotriene B4 synthesis, a powerful chemotactic agent (Serhen et al, 1984;Reibman et al, 1986). Colchicine reduces adhesion of neutrophils to endothelium inhibiting polymorphonuclear leucocyte (PMN) function (Firdham et al, 1981), E-selectin-mediated endothelial (Asako et al, 1992) and l-selectinmediated neutrophilic adhesiveness (Cronstein & Weissman, 1993;Cronstein et al, 1995). It has been reported that colchicine blocks the cyclooxygenase-2 (COX-2) activity, prostaglandin E 2 and thromboxane A 2 synthesis of mononuclear phagocytes with subsequent reduction of swelling and pain in gout and Familial Mediterranean Fever (FMF) (Pouliot et al, 1998).…”
Section: Introductionmentioning
confidence: 99%